"Because you've got faith it doesn't mean that you've got wings on your back": a qualitative analysis of the accounts of Christian prisoners serving time for a sexual offence. Issue 2 (4th May 2018) - Winder, Belinda; Blagden, Nicholas; Lievesley, Rebecca
ABSTRACT: Religious beliefs have been variously promulgated as both protective and risk factors for sexual reoffending. Moreover, therapists working with religious prisoners struggle with unravelling cognitive distortions embedded within religious views, with concerns about accusations of prejudice salient in their mindset. This paper presents a novel contribution to research by combining the qualitative analysis of the accounts offered by individuals ( n  = 12) convicted of sexual offences who describe themselves as Christians. Data were collected through semi-structured interviews and analysed using Interpretative Phenomenological Analysis. This paper focuses on two superordinate themes: (i) The God Effect and (ii) The Shadow Side of Religion. Implications of this research are discussed with reference to the assessment of dynamic risk and protective factors with religious individuals who have been convicted of a sexual offence.